2006
DOI: 10.1007/s00330-006-0507-8
|View full text |Cite
|
Sign up to set email alerts
|

The pancreas in β-thalassemia major: MR imaging features and correlation with iron stores and glucose disturbunces

Abstract: The study aims at describing the MR features of pancreas in beta-thalassemia major, investigating the relations between MR findings and glucose disturbances and between hepatic and pancreatic siderosis. Signal intensity ratios of the pancreas and liver to right paraspinous muscle (P/M, L/M) were retrospectively assessed on abdominal MR imaging studies of 31 transfusion-dependent patients with beta-thalassemia major undergoing quantification of hepatic siderosis and 10 healthy controls, using T1- (120/4/90), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
60
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 34 publications
15
60
1
2
Order By: Relevance
“…It is known that pancreatic hemosiderosis results in abnormal MRI signal intensity, and there is iron overload in the pancreas in up to 75-100% of thalassemia major cases. [7][8][9] The signal intensity ratio results showed correlation with ferritin levels 9 and also related to iron load in other organs. 7 They also correlated with exocrine pancreatic secretion function 9 and endocrine function as assessed by oral glucose tolerance test (OGTT).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…It is known that pancreatic hemosiderosis results in abnormal MRI signal intensity, and there is iron overload in the pancreas in up to 75-100% of thalassemia major cases. [7][8][9] The signal intensity ratio results showed correlation with ferritin levels 9 and also related to iron load in other organs. 7 They also correlated with exocrine pancreatic secretion function 9 and endocrine function as assessed by oral glucose tolerance test (OGTT).…”
Section: Resultsmentioning
confidence: 87%
“…Our study showed that pancreatic atrophy (volume) was a better predictor of diabetic status than pancreatic hemosiderosis (T2*). In other studies, MRI documented pancreatic fatty replacement has also been shown to predict diabetes 8 Pancreatic damage represents an irreversible, cumulative destruction of ␤ cells 15 and pancreatic atrophy is a common finding in all diabetes patients irrespective of etiology. 16 Unlike the heart or liver, the pancreas may not regenerate or remodel even with reduction in hemosiderosis.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Recently, with the use of magnetic resonance imaging (MRI) not only can the total body iron be evaluated, but organ-specific iron assessments, particularly the heart, can be acquired (3)(4)(5)(6)(7). This allows the tailoring of chelation therapy.…”
mentioning
confidence: 99%